(untitled) (Journal of history, 2019)
Turks-Meskhetians refer to a transnational ethnic group whose identity was formed as result of the group’s accommodation practices to the changing external environments necessitated by the critical conditions of survival strategies development and adherence to identities prescribed by external regimes within the frameworks of limited choice. Internal political -administrative imperatives dictated by external geopolitical strategies conditioned the names of territorial units and ethnic groups living there. The Turks Meskhetians have been involved in lengthy, and so far unsuccessful debate on their right of return to their historical homelands, rather than dealing with healings of collective traumas. The paper is aimed to create an integrative scheme of the role of interplay of international, national and ethnic in-group-related factors in repatriation and integration decisions’ making process.